2011
DOI: 10.1128/jvi.00364-11
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequence Determinants of a Coupled Termination-Reinitiation Strategy for Downstream Open Reading Frame Translation in Helminthosporium victoriae Virus 190S and Other Victoriviruses (Family Totiviridae)

Abstract: The genome-length, dicistronic mRNA of the double-stranded RNA fungal virus Helminthosporium victoriae virus 190S (genus Victorivirus, family Totiviridae) contains two long open reading frames (ORFs) that overlap in the tetranucleotide AUGA. Translation of the downstream ORF, which encodes the RNA-dependent RNA polymerase (RdRp), has been proposed to depend on ribosomal reinitiation following termination of the upstream ORF, which encodes the capsid protein. In the current study, we examined the RNA sequence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 50 publications
(93 reference statements)
2
83
1
Order By: Relevance
“…Although the positive strand of the RnVV1 genome possesses the pentamer (UAAUG) separating the two ORFs, in place of the tetramer, it has the stem I and stem II (Fig. 1E) that are well conserved in victoriviruses (54). Furthermore, three stemloop structures can be formed immediately downstream of the pentamer, which may also be important for the coupled translation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the positive strand of the RnVV1 genome possesses the pentamer (UAAUG) separating the two ORFs, in place of the tetramer, it has the stem I and stem II (Fig. 1E) that are well conserved in victoriviruses (54). Furthermore, three stemloop structures can be formed immediately downstream of the pentamer, which may also be important for the coupled translation.…”
Section: Discussionmentioning
confidence: 99%
“…Like other members of the genus Victorivirus, RnVV1 likely expresses RdRp as an independent protein product probably via the termination-reinitiation mechanism. As shown by Li et al (54), many victoriviruses have a tetranucleotide (AUGA) in which the first triplet is considered to serve as the start codon of the downstream RdRp ORF and the last triplet serves as the stop codon of the upstream CP ORF. The same authors demonstrated that the 32-nt sequence immediately upstream of the tetramer that potentially forms a pseudoknot structure is important for the reinitiation translation of HvV190S RdRp (54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pseudoknot structure usually facilitates pausing of the translating ribosome and increasing the frequency of frameshifting (35). Moreover, the pseudoknot structure commonly exists in dsRNA mycoviruses belonging to the family Totiviridae (36). Thus, LdsRNA probably represents a novel dsRNA mycovirus and was tentatively named SsMBV1 (Sclerotinia sclerotiorum megabirnavirus 1).…”
Section: Resultsmentioning
confidence: 99%